THE EFFECTS OF AI ON STUDENTS & TEACHERS AND VALUE TO CLASSROOMS AND SCHOOL LIBRARIES (AUN INTERNATIONAL CONFERENCE, 2024)
Artificial Intelligence has gradually become more essential aspect of our daily lives, and it does, have the potential to transform the way we work, exchange ideas, and gain knowledge. Based on this, the paper seeks to examine its effects in education, as well as the challenges both teachers and students face while using the AI. Media Ecology theory was used to guide the study. Findings from the study revealed that AI has provided students with a more personalized and engaging learning experience in education, and also facilitate instructors to meet the students need. The paper however concludes that the incorporation of Artificial Intelligence into the classroom has the ability to revolutionize the way students gain knowledge and how educators train. And thus, recommends that; libraries should work intimately with artificial intelligence developers to guarantee that the statistics used for training algorithms is assorted and diplomatic to all library consumers